2022
DOI: 10.1128/spectrum.00998-22
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics Analysis Reveals Aberrant Metabolism and Immunity Linked Gut Microbiota with Insomnia

Abstract: Our study indicated that systematic inflammation and metabolites might be a pathway linking the gut microbiome with insomnia. These findings provide new insights and a better understanding of gut microbiota's role in insomnia as well as potential novel microbiome-related etiologies for insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Insomnia is an important nervous system disease. Many studies have reported that drug intervention can improve the metabolic abnormalities of enterobacter, enterococcus, brucella, and other bacteria and correct the phenomenon of intestinal flora disorder ( Feng et al., 2023 ; Song et al., 2021 ; Wang et al., 2022 ). However, most of the previous studies involved the quantitative detection of intestinal flora, but no conclusion of causality between them was made.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia is an important nervous system disease. Many studies have reported that drug intervention can improve the metabolic abnormalities of enterobacter, enterococcus, brucella, and other bacteria and correct the phenomenon of intestinal flora disorder ( Feng et al., 2023 ; Song et al., 2021 ; Wang et al., 2022 ). However, most of the previous studies involved the quantitative detection of intestinal flora, but no conclusion of causality between them was made.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions and consequences have a cumulative effect on insomnia. Multiple attempts have been made to build models to interpret and explain the onset and evolution of insomnia; nevertheless, these models are insufficient to represent comprehensive knowledge ( Reynolds et al., 2017 ; Gao et al., 2019 ; Cai et al, 2021 ; Jiang et al., 2022 ; Wang Q. et al., 2022 ; Zeng et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, chronic sleep deprivation is linked to higher levels of IL-1 and TNF-α in the brain, as well as higher levels of IL-6 in the blood during the day. According to research ( Wang Q. et al., 2022 ), people with acute and chronic insomnia disorders have lower abundances of several anaerobic gut flora taxa, including Lachnospira , Roseburia , and Prevotella 9 . We discovered that the genera Prevotella7 (ID:11182) and Lachnoclostridium (ID:11308) are associated with a significant incidence of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of shift workers, sleep and circadian rhythm disturbances were also found to alter the diversity of gut microbiota (Reynolds et al., 2017). In addition, in patients with insomnia with different Tradition Chinese Medicine (TCM) syndromes, there are also differences in the dominant bacteria of the intestinal flora, and this difference may affect the occurrence, development, and outcome of different TCM syndromes (Wang et al., 2022d). These studies have shown that the sleep‐wake cycle and circadian rhythm disorders can affect the composition and diversity of gut microbiota.…”
Section: The Relationship Between Gut Microbiota and Circadian Rhythmsmentioning
confidence: 99%